Pante Gola Sebagai Kearifan Lokal Masyarakat Dusun Lambur, Desa Pangga, Kecamatan Kuwus, Kabupaten Manggarai Barat Nusa Tenggara Timur - Joni, Erni Arsi Sarina; Kaler, I Ketut; ., Aliffiati (Sunari Penjor : Journal of Anthropology; Vol 5 No 2 (2021)DO - 10.24843/SP.2021.v5.i02.p06, 2022)
Pante gola is a job of tapping palm mayang bunches to get sap which will be processed into brown sugar, either in the form of sticks (gola malang) or in the form of flour (gola rebok). Pante gola is also a tradition, regional identity and is also one of the main and side livelihoods for the people of Lambur, Pangga Village, Kuwus District, West Manggarai Regency, East Nusa Tenggara. Pante gola is very unique because this work has social values, culture, beliefs, myths, rituals/ceremonies and local wisdom that are people's beliefs. Pante gola also has many benefits in daily life, in addition to the sugar products that can be used as food sweeteners, drinks and herbal medicines for certain diseases, the sugar products can also be sold to increase people's income, so as to realize social welfare for the people of Lambur Hamlet. The theory used in this study is the theory of cultural value orientation from Kluchkon. The concepts used in this study are the concept of pante gola, local wisdom and influence. This study uses a qualitative method with an ethnographic research model, while the data sources are primary data sources and secondary data sources. Data collection techniques include observation, interviews and literature study. The researcher became the main research instrument assisted by interview guides, voice recording equipment, cameras and stationery.